SWAT-S: A SWAT-salinity module for watershed-scale modeling of natural salinity. (January 2021) - Maleki Tirabadi, Mohammad Sadegh; Banihabib, Mohammad Ebrahim; Randhir, Timothy O.
Abstract: Salinity is a complex process in watersheds, and there is a need for data and modeling salinity in arid and semi-arid watersheds. Development and application of a salinity model to accurately predict the salinity processes are difficult tasks at the watershed scale. Available salinity models are limited in sufficiently modeling natural salinity processes in watersheds. In this study, a salinity module is proposed for the Soil and Water Assessment Tool (SWAT) utilizing new salinity equations to model natural salinity processes in watershed systems. Data related to the distribution maps of saline formations is used in the modeling process. An advantage of this module is that it can use low-quality maps for salinity modeling of different salts. The proposed methodology can be used to assess the impacts of management practices, climate change, and land-use changes on non-point source pollution at a watershed scale. Graphical abstract: Image 1 Highlights: A salinity module was developed for the SWAT model for natural salinity modelling. Saline formations were included using the adjustable GIS maps. The salt transportations were simulated for the assessment of salt loadings. Interactions between solid and dissolved salts were considered for soil and river.